2018
DOI: 10.1002/aur.1997
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in social attention in autism spectrum disorder

Abstract: Although reduced social attention and increased nonsocial attention have been reported in individuals with autism spectrum disorder (ASD), the studies have relied on predominantly male samples and have been underpowered to examine sex differences. These processes may differ for females with ASD, who have been shown to be dissimilar to males in social motivation and nonsocial features, including circumscribed interests (CI). The goal of this study was to compare social and nonsocial visual attention between mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 48 publications
6
74
5
Order By: Relevance
“…Contrary to our predictions, we found no correlation between gender and any aspect of visual exploration of our stimuli. The few previous studies that found an effect of gender on social processing in autism mainly focused on infants and children [ 38 , 44 49 ]. The absence of gender effect in our sample thus calls for a developmental perspective on the interaction between gender and social attention in autism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our predictions, we found no correlation between gender and any aspect of visual exploration of our stimuli. The few previous studies that found an effect of gender on social processing in autism mainly focused on infants and children [ 38 , 44 49 ]. The absence of gender effect in our sample thus calls for a developmental perspective on the interaction between gender and social attention in autism.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a growing interest in gender differences in autism, only a few eye-tracking studies controlled for the effects of gender on social processing in autism [ 38 , 44 49 ]. Most of these studies (mainly based on child samples) suggest a potentially higher social attention in autistic females compared to autistic males.…”
Section: Introductionmentioning
confidence: 99%
“…Chawarska et al [30] reported enhanced attention to social stimuli—including faces—in female infants at high risk for ASD. Harrop and colleagues [31] reported more normative patterns of social attention in ASD females when faces were paired with images of common circumscribed interests, suggesting that compared to ASD males, they were less influenced by non-social stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not seem that there was a ceiling effect, since there were significant differences in slope across categories, as well as noticeable decreases in accuracy and increases in reaction time across array sizes, future studies may wish to compare category task performance with a scrambled-distractor paradigm to performance with an othercategory paradigm. Finally, the number of female participants was too small to assess sex effects in the analyses, which may be informative given the sex imbalance in ASD and the possibility that there is a difference in the effects of interests on behavior across sex (Harrop et al, 2018).…”
Section: Discussionmentioning
confidence: 99%